Efeito do Fucoidam de Fucus vesiculosus em um modelo experimental de artrite reumatóide - Xavier, Caroline Addison Carvalho (2005)
Rheumatoid arthritis (RA) is systemic auto imune disorder. It is caracterized by chronic inflammation of joints leading to progressive erosion of cartilage and bone. We investigated the effect of the administration of fucoidan, sulfated polysaccharides, from algae Fucus vesiculosus in the acute (6h) in zymosan-induced arthritis (AZy). Wistar rats (180-230 g) were used for all groups experimental. Non-treated animals received just intraarticular injection of 1 mg the zymosan, control group received intraarticular injection of 50 µL the saline, groups received either fucoidan of Fucus vesiculosus (15, 30, 50 or 70 mg/Kg) or parecoxib (1 mg/Kg) 1 hour after injection of zymosan. After 6 h, the articular exudates were collected for evaluation of the cell influx and nitrite (Griess reaction) release. The sinovial membranes and articular cartilages were excised for histopathological analysis and by determination of the glycosaminoglycan (GAG), respectively. ZyA led to increased NO and cell influx into the joints. Therapeutic administration of the fucoidan or parecoxib did significantly inhibited the cell influx and the synovitis, as compared to non-treated rats (p<0,05), though being able to reduced NO release. Representative agarose gel electrophoresis of the GAGs, the content of condroitin-sulphate was observed during the process. These findings suggest that the fucoidan from Fucus vesiculosus has potential anti-inflammatory activity